1996
DOI: 10.1136/emj.13.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic pneumothorax: is a chest drain always necessary?

Abstract: (_JAccid EmergMed 1996;13:173-174)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 7 publications
0
41
0
2
Order By: Relevance
“…Most surgeons and emergency physicians will place a chest tube in occult and nonoccult traumatic pneumothoraces. However, studies suggest that carefully selected patients may be treated conservatively ultimately requiring chest tube placement only in about 10% of cases [86]. If positive pressure ventilation is anticipated, placement of a chest tube is mandatory.…”
Section: Traumatic Noniatrogenic Pneumothoraxmentioning
confidence: 99%
“…Most surgeons and emergency physicians will place a chest tube in occult and nonoccult traumatic pneumothoraces. However, studies suggest that carefully selected patients may be treated conservatively ultimately requiring chest tube placement only in about 10% of cases [86]. If positive pressure ventilation is anticipated, placement of a chest tube is mandatory.…”
Section: Traumatic Noniatrogenic Pneumothoraxmentioning
confidence: 99%
“…Recently, the necessity of chest drain insertion for a proportion of traumatic pneumothoraces has been challenged. 2 The justification for this proposed change is the high complication rate some authors associate with tube thoracostomy. [3][4][5][6] These complications can be categorised as insertional, positional, or infective.…”
mentioning
confidence: 99%
“…The incident rate of CTD varied from 31 [33] to 67% [29] of traumatic pneumothorax patents, and up to 82% for patients with concurrent pneumothorax and hemothorax [34]. However, some studies suggest that carefully selected patients may be treated conservatively, ultimately requiring CTD only in about 10% of cases [19,35]. This large variance in practice reflects the difficulty clinicians have in determining the appropriate treatment for pneumothorax.…”
Section: Multidetector Computed Tomography Management Of Pneumothoraxmentioning
confidence: 92%
“…Some studies suggest that it is not safe to manage patients with small occult pneumothoraces without CTD [43], whereas some suggest that small overt pneumothoraces can be managed without CTD [44]. Some found that not only small, but also moderate-sized traumatic pneumothoraces could be managed without CTD, in the absence of other significant injuries or respiratory compromise [35,45]. Additionally, the two randomized clinical trials in the literature have conflicting results; OPTX patients with positive pressure ventilation (PPV) would need CTD [41], versus all traumatic OPTXs could be managed safely without CTD [46], despite positive pressure ventilation.…”
Section: Multidetector Computed Tomography Management Of Pneumothoraxmentioning
confidence: 97%